Kajian Rumput Vetiver Sebagai Pengaman Lereng Secara Berkelanjutan - Susilawati, Susilawati; Veronika, Veronika (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
Flores is the island in the NTT province, which has a row of volcanoes, with the mountainous topography. Transportation is state road, along the coast with high cliffs on the other side. That often causes problems during the rainy season as several landslides. Various methods are used to overcome this landslide. Studies on vetiver grass as slope protection done to secure the slopes on a sustainable basis. First, an evaluation done for the slope construction along the slope safety from Nangaroro to Aegela, which are using vetiver grass as a safety slopes in addition to other security structures. It is also done for the same job of the road from Ende to Nangaroro and Ende-Detusoko. This study covers the technical aspects, ecological, construction and sustainability of the infrastructure that has been built. Furthermore, it is done the literature study to find more appropriate method, environmentally friendly and sustainable in securing these slopes problematic. From the literature studies and the field survey done, it can be concluded and recommended several models of eco-friendly structural design of vetiver grass and geotextile for slope protection, which is based on technical-meet standard strength, ecologically-friendly environment, locally-developed local wisdom, so it is easy to construct.